Pemanfaatan Teknologi Artificial Intelligence (AI) dalam Digitalisasi Pembelajaran untuk Meningkatkan Literasi Digital Siswa - Lukman Lukman; Herwandi Sape; Habiba Ulfahyana (Cerdas: Jurnal Ilmu Pendidikan Sosial dan Humaniora, 2025)
This study aims to analyze the effect of utilizing Artificial Intelligence (AI) technology in the digitalization of learning on improving the digital literacy of Grade X students in the Computer and Network Engineering (TKJ) program at SMK Maros. The research employed a quantitative approach with an experimental method using a pre-experimental design, specifically a one-group pretest–posttest design. The research population consisted of all Grade X TKJ students totaling 42 individuals, who were simultaneously used as the research sample through a saturated sampling technique. Data were collected through a digital literacy test and observations of the learning process. Quantitative data were analyzed using descriptive and inferential statistical techniques. The results indicate that the utilization of AI technology in digital learning has a significant effect on improving students’ digital literacy. This is evidenced by an increase in the mean digital literacy scores from the pretest to the posttest, as well as the results of the paired sample t-test, which showed a significance value of less than 0.05. In addition, observational findings revealed increased student engagement, participation, and positive attitudes during AI-based learning activities. Therefore, it can be concluded that AI-based digital learning is effective in enhancing students’ digital literacy and is relevant for implementation in schools to support students’ readiness in facing the challenges of the digital era.